DSM-5 full syndrome, other specified, and unspecified eating disorders in Australian adolescents: prevalence and clinical significance. Issue 6 (2nd April 2020) - Mitchison, Deborah; Mond, Jonathan; Bussey, Kay; Griffiths, Scott; Trompeter, Nora; Lonergan, Alexandra; Pike, Kathleen M.; Murray, Stuart B.; Hay, Phillipa
Abstract: Background: Little information is available on the prevalence of Diagnostic and Statistical Manual of Mental Disorders (DSM)-5 eating disorders in adolescence, and eating disorders remain unique in the DSM for not systematically including a criterion for clinical significance. This study aimed to provide the first prevalence report of the full suite of DSM-5 eating disorders in adolescence, and to examine the impact of applying a criterion for clinical significance. Methods: In total, 5191 (participation rate: 70%) Australian adolescents completed a survey measuring 1-month prevalence of eating disorder symptoms for all criterial, 'other specified' and unspecified eating disorders, as well as health-related quality of life and psychological distress. Results: The point prevalence of any eating disorder was 22.2% (12.8% in boys, 32.9% in girls), and 'other specified' disorders (11.2%) were more common than full criterial disorders (6.2%). Probable bulimia nervosa and binge eating disorder, but not anorexia nervosa (AN), were more likely to be experienced by older adolescents. Most disorders were associated with an increased odds for being at a higher weight. The prevalence of eating disorders was reduced by 40% (to 13.6%) when a criterion for clinical significance was applied. Conclusions: Eating disorders, particularly 'other specified' syndromes, are common in adolescence, and are experienced across age, weight, socioeconomic and migrant status. The merit of adding a criterion for clinical significance to the eating disorders, similar to other DSM-5 disorders, warrants consideration. At the least, screening tools should measure distress and impairment associated with eating disorder symptoms in order to capture adolescents in greatest need for intervention.